Self Efficacy with Smartphone Use among Adolescent Girls: A Cross Sectional Study in Surabaya - Nety Mawarda Hatmanti; Melina Kussumawati; Lono Wijayanti; Iis Noventi (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Self-efficacy in adolescents is recognized as an important psychological trait closely associated with success in learning and adaptive behavior. In the era of Society 5.0, adolescent self-efficacy has attracted increasing attention, particularly in relation to smartphone usage habits within the context of online learning. This study aimed to analyze the relationship between self-efficacy and smartphone use among adolescent girls. A correlational analytic design was applied. The study population consisted of all female adolescents in Surabaya (N=235,687), and a total of 400 respondents were selected through cluster random sampling. The independent variable was self-efficacy, and the dependent variable was smartphone usage. Data were collected using the General Self-Efficacy Scale (GSE) and a smartphone usage questionnaire. The data were analyzed using the Spearman rank correlation test with a significance level of α = 0.05. The results showed that 72.3% of the respondents had moderate levels of self-efficacy, while 59.5% reported high levels of smartphone use. The Spearman test revealed a statistically significant but weak positive correlation between self-efficacy and smartphone use (r=0.192, p=0.000). These findings indicate that although a relationship exists between self-efficacy and smartphone use among adolescent girls, the strength of the association is limited. Therefore, interpretations suggesting that higher self-efficacy directly leads to more positive smartphone use should be made cautiously, as this is not strongly supported by the data. The involvement of families and educators remains essential in guiding adolescents toward constructive and responsible smartphone use.